Use of measurement tools for screening of postoperative delirium in nursing practice - Balková, Mária; Tomagová, Martina (Central European Journal of Nursing and Midwifery, 2018)
Aim: The aim of the literary overview was to search quantitative research studies focusing on screening for postoperative patient delirium by nurses with the aid of measurement tools; and, afterwards, to compare the tools used with respect to their psychometric characteristics and use in clinical nursing practice. Design: Overview study –literary review. Methods: Electronic databases were searched for relevant documents (i.e., Web of Science, SCOPUS, Science Direct, and Summon Discovery Tool), from the period1990–2017. Key words used for databases were: postoperative delirium, screening, tool, validity, reliability, psychometric characteristic, and nursing, combined with Boolean operators. Results: A total of 253 documents were identified. Based on the chosenselection criteria, eight studies dealing with screening of postoperative delirium were included in the analysis and overview. The following measurement tools were used in the studies: the Confusion Assessment Method for Intensive Care Units –CAM-ICU, the Nursing Delirium Screening Scale –Nu-DESC, the NEECHAM Confusion Scale, the Delirium Observation Screening Scale –DOSS,andthe Intensive Care Delirium Screening Checklist –ICDSC. The tool with the optimum psychometric characteristics for detection ofpostoperative delirium is the CAM-ICU tool. Conclusion: The results of the studies analysed indicate the importance of the implementation of a relevant tool for screening of postoperative delirium. It is essential to examine the psychometric characteristics and usability ofscreening tools in Slovak clinical practice.
Keywords: Confusion; ošetřovatelská péče; Postoperative Complications; Risk Factors; Emergence Delirium; Humans; pooperační delirium; lidé; pooperační komplikace; zmatenost; Delirium; Nursing Care; rizikové faktory; delirium